A case of pituitary apoplexy with unusual presentation (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Pituitary apoplexy is a rare but potentially life-threatening condition caused by either haemorrhage or infarction of the pituitary gland. It commonly occurs in non-functioning pituitary adenoma. Patients present with the clinical syndrome of headache, visual defects or ophthalmoplegia, altered consciousness and variable endocrine deficits. However, the condition may also be subclinical, like in our case, where the presenting feature was mild to moderate headache for a few months, misguiding the physician. Her prolactin level was high, and an MRI revealed evidence of haemorrhage within the pituitary gland. Her amenorrhoea persisted even after normalization of prolactin, which may be related to reduced LH and FSH after apoplexy. The case is reported because of its simplicity of presentation, which we should not ignore.J Assoc Clin Endocrinol Diabetol Bangladesh, July 2024;3(2): 67-70